Dynamic ferritin levels and survival outcomes in secondary hemophagocytic syndrome: a comprehensive analysis - Koymen, Gorkem; Kilincer Bozgul, Sukriye Miray; Kurtulmus, Ilkce Akgun; Akad Soyer, Nur; Ak, Gunes; Bozkurt, Devrim; Gunes, Ajda; Yargucu Zihni, Figen (Frontiers in Medicine, 2025)
BackgroundHemophagocytic syndrome (HPS) is a life-threatening condition characterized by excessive immune activation and cytokine release. Reliable prognostic markers to guide clinical management and predict outcomes are lacking. This study aims to evaluate the prognostic ability of dynamic ferritin levels in patients with HPS and their potential role in guiding treatment modifications.Materials and methodsWe conducted a retrospective cohort study including 99 patients diagnosed with HPS between January 2013 and June 2022. Data on demographic characteristics, clinical presentations, treatment modalities, and laboratory values were collected, including ferritin levels at diagnosis and during treatment. Statistical analyses including Cox proportional hazards models were used to assess the risk factors of mortality, and a receiver operating curve analysis was conducted to assess the association between ferritin level changes and survival outcomes.ResultsPatients exhibiting a decrease in ferritin levels within the first week of treatment had significantly improved survival rates compared to those with increasing levels (p < 0.05). Multivariate analysis identified early ferritin level reduction as an independent predictor of better survival outcomes (HR 0.62, 95% CI: 0.41–0.93, p = 0.02). Notably, decreases below 7.54% in ferritin levels from day 0 to day 3 were associated with 85.19% sensitivity and 57.14% specificity for survival prediction (AUC = 0.684), while increases >36.67% from day 0 to day 5 showed 50.0% sensitivity and 85.0% specificity for mortality prediction (AUC = 0.697). Additionally, the liver injury group demonstrated significantly higher ferritin levels and D-dimer values, with lower fibrinogen and albumin levels compared to the non-liver injury group.ConclusionThe improved survival associated with early decreases in ferritin levels highlights the potential of ferritin monitoring to guide clinical decision-making and treatment adjustments. Based on the results, the integration of ferritin level dynamics into HPS management protocols could improve patient outcomes.